Fort Cochin in Kerala, 1750-1830 : the social condition of a Dutch community in an Indian milieu - Singh, Anjana, 1976- (TANAP monographs on the history of the Asian-European interaction ;, 2010)
This study of the early modern fortress town of Cochin in India, based on the rarely used VOC archival deposits in the Tamilnadu State Archives in Chennai (Madras), provides an intimate portrait of a Dutch urban community of East India Company servants and their dependents living within the larger social environment of the Malabar coast. It shows how between 1750 and 1830 the population of this Dutch settlement had adapted itself to the fundamental political and economic changes that occurred as a result of local state formation processes, the demise of the Dutch East India Company, and the ...